Новые и малоизвестные цикадовые семейства Cixiidae (Homoptera, Auchenorrhyncha) Кавказа и Закавказья - Логвиненко, В.Н. (Вестник зоологии, 1969)
On the basis of the Transcaucasian expedition data, in particular concerning the Cixiidae family, some species, new for science, are detected: Cixius (Ceratocixius) rujus sp. n., C. (Orinocixius) hylaeus sp. n., C. (Tetracixius) brachydentus sp. n., Hyalesthes ve-nustus sp. n., as well as a number of rare and insufficiently known representatives of the Cixius genus, some of which are observed in the territory of the USSR for the firist time.